Recycle - Barnham, Kay. (London : Wayland, 2006)
Explains how recycling helps the environment; describes the benefits of reusing and recycling glass, plastic, aluminum, paper, and other materials; and presents suggestions for recycling at home and at school.
Includes index.
4.7
3-6.
3-6
Keywords: Recycling (Waste, etc.) -- Juvenile literature; Recycling (Waste); Recycling